Analysis of the influence of farmers' knowledge skills and attitudes towards extension in understanding the capacity of Madurese cattle farmers in West Waru Village, Pamekasan Regency - Triyasari Sri Ratna; Kamilah Istifadatul (BIO Web of Conferences)
Livestock businesses in West Waru Village tend to apply traditional treatment techniques rather than using scientifically measured rules. Even scientifically sound methods may be inefficient economically and nutritionally, leading to high costs, particularly in feed procurement. The purpose of this study is to identify the characteristics of breeders that influence the performance of feed supply management in the beef cattle business and to examines factors such as knowledge transfer, skill, and attitude of extension methods within the beef cattle industry. The sampling technique using Roscoe theory and snowball sampling obtained as many as 50 respondents. The analysis method used to answer the first goal is multiple linear regression analysis and then the second goal uses qualitative descriptive. The results showed that knowledge and attitude has a significant impact to breeder welfare. Breeders who participated in extension activities demonstrated an improved understanding of livestock management, including the importance of proper feeding, record-keeping, and maintaining cleanliness in livestock and their surroundings. This improved knowledge and positive attitude towards livestock management were found to be crucial factors in enhancing the welfare of the breeders.